Diverse functions of the ecdysone receptor (EcR) in the panoistic ovary of the German cockroach. (May 2023) - Rumbo, M.; Pagone, V.; Piulachs, M.D.
Abstract: Ecdysone regulates essential processes in insect life. Perhaps the most well-known of these are related to metamorphosis. However, ecdysone is also required to regulate the proliferation and differentiation of germ cells in the ovary. The role of ecdysone in insect oogenesis has been studied in depth in holometabolan species with meroistic ovaries, such as Drosophila melanogaster, while in hemimetabolan species with panoistic ovaries their functions are still poorly understood. In the present work, we studied the role of ecdysone in the ovary of the last nymphal instar of the cockroach Blattella germanica by using RNA interference to reduce the levels of the ecdysone receptor ( EcR ), and thereby deplete the expression of ecdysteroidogenic genes in the prothoracic gland. However, the expression of ecdysteroidogenic genes was upregulated in the ovary, resulting in cell overproliferation in the germarium, which appeared swollen. By analysing the expression of genes that respond to ecdysone, we found that when the source of 20E is the nymphal ovary, EcR appears to repress 20E-associated genes bypassing early genes signalling. Graphical abstract: Image 1 Highlights: In nymphal ovaries of B.germanica, EcR depletion increases ecdysteroidogenic gene expression. EcR can be repressor or activator of ecdysone-dependent genes depending on the tissue. In nymphal ovaries, EcR transduces 20E signal in different ways depending on the 20E source.